(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Agricultural soils are the major source of the potent greenhouse gas and ozone-depleting substance, N2O. An incubation study was carried out using the volcanic ash fine textured soil of Shintoku. Soil samples used in this study were taken from managed grassland at Shintoku Experimental Livestock Farm of Hokkaido University in Southern Hokkaido, Japan (N43º05′, E142º51′). Soil aggregates were air-dried, and sieved with 4.5 mm and 2 mm and adjusted the soil moisture of 60% and 80% of field water capacity (FWC). Just after the moistening, the aggregates were incubated for 9 days under a temperature of 20°C. Just after starting the incubation, the flush of N2O production was observed. Similar flushes of carbon dioxide (CO2) and nitric oxide (NO) productions were also observed. All of the gas productions were higher in larger aggregates with 80% of field water capacity. The concentrations of Water Extractable Organic Carbon (WEOC), NH4+-N, pH and total N were significantly different before and after incubation. Shintoku soil showed a significant correlation between before and after incubation for all soil chemical properties except pH. Especially WEOC and NH4+-N changed immediately after the addition of water and this situation continued during the incubation. Larger aggregates showed higher amounts of NH4+-N and NO3-–N and were responsible for higher N2O production compared to smaller aggregates. In Shintoku the results of N2O-N/NO-N ratio in both moisture contents indicated nitrification as a main process of N2O production. It is very well known that N2O is produced more from the denitrification process than nitrification. Poor aeration and less diffusion of NO3-N and WEOC from the aerobic area to the anaerobic area reduce N2O production in the denitrification process of fine textured Shintoku soil. Int. J. Agril. Res. Innov. Tech. 14(2): 99-110, December 2024